A corporate strategy for Software AG Phils., Inc. - Niego, Noel V. (Animo Repository, 1997)
The software services sector is one of the priority areas defined by government for export development and quest in becoming the IT hub in Asia. Because of this, the government provider incentives to exporters of software services, like Income Tax Holiday for 4 years, Tax and Duty Exemption on Imported Capital Equipment, and the Employment of Foreign Nationals. Philippine Software Association (PSA) claims that 70% of the total industry output is from software exports. It was projected that the Philippines will have an export of $300 million in year 2000. PSA estimates that less than 50 software service companies are serious players. The industry is dominated by small companies where 52% of the companies has less than 50 personnel. The global market favor software companies with a minimum size of 200 personnel. The PSA member companies operate extensively in Southeast Asia and some parts of USA, Canada, Australia, and Europe. The inexpensive labor rates, technical expertise and proficiency in English enable Filipinos to compete in the international market. With more than 40, 000 graduates of computer-related courses, only 25% of these students will pass the aptitude examinations given by companies. There is a need to upgrade and reorient the courses toward the skills that are in demand. The governments campaign towards government and private use of Information Technology proves to be a major opportunity to the local software services companies. The governments projects alone cost almost 2 billion within a five-year period. This means that an average of P400 million a year is projected to be the IT demand from the government. Projections from International Data Corporation placed the global market computer software and services to be $360 billion as of last year alone. HP estimated that IT spending in Singapore, Malaysia, and Indonesia will reach the $1o billion mark by year 2000. The shortage of manpower to produce all these requirement is major problem in most of the developed countries. This is a great opportunity for the Philippine software services companies to enter the global software market. Software AG Philippine provides IT solutions to clients. This study was initiated to provide software services to the growing business of the company and to take advantage of the government demands for software services. SAG Philippines will provide its quality products and technical skills in the requirements of software industry. The corporate strategy will include the focus on system integration and alliances to some industry leaders like IBM, Hewlette-Packard, Microsoft Corp., Digital Equipment Corp. and SAP. The purpose of the alliance is to strengthen their market presence and to complement each others services. In the functional level, the company will promote its competitive advantage by beefing up the departments of Sales and Marketing, Finance and Administration and Professional Services. Strategy for Sales and Marketing includes the hiring of qualified personnel, service focus, target and market and focus on system integration. The finance includes the adoption of management control system. Lastly, Administration and Professional Services include the upliftment of the welfare of the employees as well as day-today service for the employees.